2015
DOI: 10.18295/squmj.2015.15.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Botryoid Rhabdomyosarcoma of the Cervix: Case report with review of the literature

Abstract: Botryoid rhabdomyosarcoma is an aggressive malignancy that arises from embryonal rhabdomyoblasts. It is commonly seen in the genital tract of female infants and young children. Due to the young age of affected patients, this malignancy poses a management challenge as the preservation of hormonal, sexual and reproductive function is essential. There is currently no consensus regarding management. However, treatment strategies for these tumours have evolved from radical exenterative surgeries to more conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Localized cervical disease is best treated with fertility-sparing procedures such as polypectomy and simple or radical trachelectomy, combined with adjuvant chemotherapy [ 10 , 12 ]. A simple total hysterectomy with ovarian conservation is recommended for patients with combined cervical and uterine involvement [ 6 , 12 ]. In the absence of parametrial involvement, radical hysterectomy is not warranted as it is associated with increased morbidity and no improvement in patient outcomes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized cervical disease is best treated with fertility-sparing procedures such as polypectomy and simple or radical trachelectomy, combined with adjuvant chemotherapy [ 10 , 12 ]. A simple total hysterectomy with ovarian conservation is recommended for patients with combined cervical and uterine involvement [ 6 , 12 ]. In the absence of parametrial involvement, radical hysterectomy is not warranted as it is associated with increased morbidity and no improvement in patient outcomes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fertility preservation is one major challenge affecting the choice of therapy. Embryonal RMS is a chemosensitive tumor and responds best to the vincristine, adriamycin, and cyclophosphamide (VAC) regime [ 6 ]. In this report, we describe a case of embryonal RMS of the uterine cervix occurring in a 24-year-old woman.…”
Section: Introductionmentioning
confidence: 99%
“…Some patient experienced additional symptoms included leukorrhea, bleeding and malodorous discharge. The patient we are reporting fulfilled all the three criteria essential for the diagnosis of botryoid variety of RMS; a polypoid appearance of the lesion, an origin below a mucous membrane-covered surface and the presence of a cambium layer [ 6 ]. Many authors recommend that any polypoidal mass found in a child be regarded as botryoid RMS unless proven otherwise [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…pelvic exenteration was considered the treatment of choice in the late 1960s, outcomes were often unsatisfactory. In the 1970s, limited surgery with adjuvant chemotherapy and/or irradiation showed improved survival [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…pelvic exenteration was considered the treatment of choice in the late 1960s, outcomes were often unsatisfactory. In the past years, limited surgery with adjuvant chemotherapy and/or irradiation showed improved survival [17]. In Sweden, pediatric RMS showed a higher rate of metastatic disease, this might explain the decreased trend in overall survival in the last decade.…”
Section: Ethics Statementmentioning
confidence: 99%